Managing Diversity Practices of Citizenship - Cardinal, Linda; Brown, Nicholas (Governance Series, 2007)
Australia, Canada, and Ireland are all engaged in questions of multiculturalism and in the politics of recognition and reconciliation, the opportunities and pressures of geographic regionalism, shifts in political agendas associated with the impact of neo-liberalism, and moves to frame political agendas less at the macro-level of state intervention and more at the level of community partnership and empowerment. Analyzing issues ranging from urban planning and the provision of broadcasting services for minority languages, to principled debates over basic rights and entitlements, these essays offer penetrating summaries of each political culture while also prompting comparative reflection on the broad theme of "democracy and difference."